Frontispiece: Enhanced Sensitivity to Local Dynamics in Peptides by Use of Temperature‐Jump IR Spectroscopy and Isotope Labeling. Issue 16 (18th March 2020) - Scheerer, David; Chi, Heng; McElheny, Dan; Keiderling, Timothy A.; Hauser, Karin
Abstract : Site‐selected dynamics of a three‐stranded β‐sheet peptide were probed by laser‐excited temperature‐jump infrared spectroscopy and isotopic labeling. Relaxation time constants showed an enhanced sensitivity to vibrational coupling. For more details, see the Full Paper by T. A. Keiderling, K. Hauser and co‐workers on page 3524 ff.